Two analyses of CSCW and groupware - Grudin, Jonathan (DAIMI Report Series, 1990)
This report consists of two papers on the topics of computer supported cooperative work and groupware. The first examines the emergence of CSCW in the mid-1980s, finding that its timing and composition reflect changes within one context of systems development, product development. Many of the issues – and some of the participants – have a history in internal systems development; some confusion of identity in the field may be traced to the merging of these development paradigms. The second paper examines eight challenges in designing and evaluating groupware or CSCW applications, challenges that are new for product or application developers. One that is particularly problematic, due to the way software products are marketed, is the need to address a range of organizational factors on a site-by-site basis to obtain acceptance of systems developed to support groups.